Grazing season overrides intensity in driving plant subordinate species-mediated community dynamics across contrasting elevations of typical steppe - Yu-Wen Zhang; Lan Li; Zhao-Xia Guo; Zhao-Ling Da; Wen-Jun Wang; Xing-Qi Wang; Fu-Jiang Hou; Ji-Zhou Ren (Global and Planetary Change, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Mechanoadaptive conductive hydrogels with dual functionalities for epidermal sEMG monitoring and diabetic wound healing - Guoqiang Ren; Jingyun Ma; Qiuyue Peng; Pengfei Liu; Xiaobo Wang; Da Li; Yuesheng Zhang; Chaonan He; Chen Huang; Honghua Ye; Yavuz Nuri Ertas; Qingbo Xu; et al. (Chemical Engineering Journal, 2026)

The transcription factor BRN2 confers cadmium tolerance by regulating SAM1 expression in Arabidopsis - Su Li; Jing Huang; Jia Qi Li; Chuan Jin Shan; Ren Fang Shen; Da Li Zeng; Jin Chen; Xian Jiao Guan; Xiao Fang Zhu; Ting Wu Liu; Yong Gang Xu (Plant Science, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Advances in understanding the MicroRNA-transcription factor regulatory network governing terpenoid biosynthesis in medicinal plants - Jingyi Xu; Yue Shi; Xiaoqian Xie; Yueting Xie; Jing Tian; Yue Ren; Yuan Li; Da Li; Chunmei Yang; Qile Zhou; Jinhui Man; Hui Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Integrative bioinformatics and machine learning to explore the mechanism of Scutellaria baicalensis Georgi in TGF-β1-induced ASMCs proliferation during asthma airway remodeling - Yue Ren; Minxuan Wu; Sihan Yu; Da Li; Linghe Zhang; Yiwen Wang; Jiayi Wang; Kaiyang Liu; Wen Qin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Methylation in ambient ion source enables direct isomer differentiation of oligosaccharides by tandem mass spectrometry - Liping Xu; Dandan Sha; Rongfan Ren; Hongli Li; David Da Yong Chen (Carbohydrate Polymers, 2026)

Multi-objective optimization study of wave elimination and electricity generation performance of Savonius hydrokinetic turbine array based on metamodel - Ruiyin Song; Haihan Yu; Congjie Ren; Xi Cui; Fengshen Li; Lei Zhang; Gao Bai; Kai Chen; Da Liu (Ocean Engineering, 2026)

Improvement of RNAi efficiency by delivering of dsRNA formulated with cell-penetrating disulfide polymer in the fall Armyworm, Spodoptera frugiperda - Xu Wu; Wen-Mei Li; Qiang Xu; Xiao-Ping Yi; Da-He Zhang; Ming-Zhe He; Yu-Hong Ren (Journal of Insect Physiology, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Tough, highly resilient and fatigue-resistant cellulose-based double-network elastomers with environmental tolerance for multi-domain sensing - Xiang Li; Shiyu Fan; Jiayi Ma; Zhengyi Zhu; Da Guan; Shixue Ren; Yanli Ma; Shujun Li (Chemical Engineering Journal, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Laboratory investigation of sandstone joints and strata on TBM performance using a tunnelling test platform - Wei-Qiang Xie; Xiao-Li Liu; Shao-Hui Tang; Qi Zhang; Da-Rui Ren; Qing Ma (Engineering Geology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Fabrication and mechanism of microspheres with tunable and control-released hydrophobicity in a wide-range: Ultra-low-density proppant - Zhenyong Li; Yang Zhou; Da Zhang; Min Xu; Rui Li; Xianyan Ren (Fuel, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

Niche Partitioning and Intraspecific Variation of Thaumarchaeota in Deep Ocean Sediments - Ronghua Liu; Xinxin He; Gaoyang Ren; Da‐Wei Li; Meixun Zhao; Laura Lehtovirta‐Morley; Jonathan D. Todd; Xiao‐Hua Zhang; Jiwen Liu (Environmental Microbiology, 2025)
Deep‐sea sediments contain a large number of Thaumarchaeota that are phylogenetically distinct from their pelagic counterparts. However, their ecology and evolutionary adaptations are not well understood. Metagenomic analyses were conducted on samples from various depths of a 750‐cm sediment core collected from the Mariana Trench Challenger Deep. The abundance of Thaumarchaeota and archaeal amoA generally decreased with depth, except for an unexpected peak midway through the core. The thaumarchaeotal metagenome‐assembled genomes were classified into diverse phylogenetic clusters associated with amoA ‐NP‐γ, amoA ‐NP‐θ, and amoA ‐NP‐δ of ammonia‐oxidising Thaumarchaeota and non‐ammonia‐oxidising lineages. The most abundant group was within amoA ‐NP‐γ, which is usually found in coastal and shallow habitats, indicating potential niche expansion from marine shallow to hadal environments. This benthic group showed within‐species genomic variations compared to the previously identified Hadal water group, suggesting microdiversification of hadal Thaumarchaeota along with niche separation between benthic and pelagic environments. Evolutionary adaptations associated with the benthic‐to‐pelagic transition included reduced genome size, loss of motility/cell adhesion, altered energy metabolism, and different mechanisms for substrate acquisition and regulation (e.g., ammonium). These findings offer new insights into the evolution of hadal Thaumarchaeota and demonstrate, for the first time, intraspecies‐level genomic variation in Thaumarchaeota related to the benthic‐versus‐pelagic niche partitioning in the deep ocean.

Relationship between MO/(SiO2+Al2O3) of materials—amorphous gel structure—properties of the one-part FA-Slag-based AAMs - Da-Wang Zhang; Tian-Tian Yang; Xiao-Guang Xu; Yi-Ren Wang; Hui Li (Journal of Environmental Chemical Engineering, 2024)

Bonding-slip behaviour of steel-concrete interfaces in CFDST members with PBL ribs - Yan-Li Shi; Jia-Xing Ren; Jia-Hao Fan; Wen-Da Wang; Hai-Cui Wang (Engineering Structures, 2024)

Gender-specific effects of polystyrene nanoplastic exposure on triclosan-induced reproductive toxicity in zebrafish (Danio rerio) - Zhiming Li; Hongyi Xian; Rongyi Ye; Yizhou Zhong; Boxuan Liang; Yuji Huang; Mingzhu Dai; Jie Guo; Shuqin Tang; Xiaohu Ren; Ruobing Bai; Yu Feng; et al. (Science of The Total Environment, 2024)

Two new lignans from the fresh roots of Zhongsheng No.1 Rehmannia glutinosa - Xiang-Da Li; Yan-Gang Cao; Yu-Han Zhang; Ying-Jie Ren; Meng-Nan Zeng; Yan-Ling Liu; Xu Chen; Xin-Yi Ma; Bing-Xian Zhao; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

From cradle to grave: Deciphering sex-specific disruptions of the nervous and reproductive systems through interactions of 4-methylbenzylidene camphor and nanoplastics in adult zebrafish - Hongyi Xian; Zhiming Li; Ruobing Bai; Rongyi Ye; Yu Feng; Yizhou Zhong; Boxuan Liang; Yuji Huang; Jie Guo; Binjie Wang; Mingzhu Dai; Shuqin Tang; et al. (Journal of Hazardous Materials, 2024)

Microcystin-RR promote lipid accumulation through CD36 mediated signal pathway and fatty acid uptake in HepG2 cells - Wenjuan Jia; Lin Zhong; Qingmiao Ren; Da Teng; Lei Gong; Haibin Dong; Jun Li; Chunxiao Wang; Yong-Xing He; Jun Yang (Environmental Research, 2024)

Assessing the coherence between performance and resource investment for the sustainable development goals in Paraguay: a data-driven hybrid method - Kuo-Jui Wu; Ren Yu; Da Zhao; Li Ma; Ming-Lang Tseng (Environment, Development and Sustainability, 2024)

Heterologous expression of taxane genes confers resistance to fall armyworm in Nicotiana benthamiana - Zhenlu Xu; Yaohua Zhai; Huimin Chang; Da Yan; Pengliang Ge; Guangming Ren; Lijun Zhang; Ye Yuan; Ruoyan Wang; Wentao Li; Fuguang Li; Maozhi Ren; et al. (Plant Cell Reports, 2024)

Inhibition of nucleotide metabolism with dual-template epitope imprinted nanoparticles for targeted HER2+ tumor therapy - Xing-Hui Ren; Lei Shi; Zi-Bo Ma; Da-Wei Wang; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Chemical Engineering Journal, 2024)

Diarylpentanoids and phenylpropanoids from the roots of Anthriscus sylvestris (L.) Hoffm - Yan-ling Liu; Yan-gang Cao; Ying Niu; Ya-juan Zheng; Xu Chen; Ying-jie Ren; Xi-ling Fan; Xiang-da Li; Xin-yi Ma; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2023)

Salviamilthone A-O, diterpenoid quinones from Salvia miltiorrhiza - Ying-Jie Ren; Yan-Gang Cao; Meng-Nan Zeng; Qin-Qin Zhang; Yan-Ling Liu; Chen He; Xu Chen; Xi-Ling Fan; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

The c-MYC transcription factor conduces to resistance to cisplatin by regulating MMS19 in bladder cancer cells - Da Ren; Lei Li; Shuai Wang; Yali Zuo (Tissue and Cell, 2023)

Enhanced selective separation of vanadium(V) and chromium(VI) using the CeO2 nanorod containing oxygen vacancies - Ruixi Lin; Jiarong Li; Xuequan Jing; Meina Guo; Guoqing Ren; Haonan Qin; Zhangwei Yao; Yinhua Wan; Weijie Song; Huifeng Zeng; Feifei Yang; Da Zhao; et al. (Environmental Science and Pollution Research, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Two new lignans from the herbaceous stems of Ephedra intermedia - Xi-Ling Fan; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Ying-Jie Ren; Xin-Yi Ma; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2023)

Constraints on ore-forming fluid evolution and guidance for ore exploration in the Zhaxikang Sb–Pb–Zn–Ag deposit in southern Tibet: insights from silver isotope fractionation of galena - Da Wang; Ryan Mathur; Youye Zheng; Hongjie Wu; Yiwen Lv; Gangyang Zhang; Ren Huan; Miao Yu; Yujie Li (Mineralium Deposita, 2022)

Synthesis of pyrazole-4-carboxamides as potential fungicide candidates - Cuntao Dong; Wei Gao; Xiaotian Li; Susu Sun; Jingqian Huo; Yanen Wang; Da Ren; Jinlin Zhang; Lai Chen (Molecular Diversity, 2021)

Correction to: TAK1 is involved in sodium L‑lactate‑stimulated p38 signaling and promotes apoptosis - Qingen Da; Zilong Yan; Zhangfu Li; Zhen Han; Mingming Ren; Lei Huang; Xiaowei Zhang; Jikui Liu; Tao Wang (Molecular and Cellular Biochemistry, 2021)

TAK1 is involved in sodium L-lactate-stimulated p38 signaling and promotes apoptosis - Qingen Da; Zilong Yan; Zhangfu Li; Zhen Han; Mingming Ren; Lei Huang; Xiaowei Zhang; Jikui Liu; Tao Wang (Molecular and Cellular Biochemistry, 2021)

Enhanced mass transfer and service time of mesh Ti/Sb-SnO2 electrode for electro-catalytic oxidation of phenol - Linlin Huang; Da Li; Junfeng Liu; Lisha Yang; Changchao Dai; Nanqi Ren; Yujie Feng (Environmental Science and Pollution Research, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Isolation and Identification of Endophytic Fungi in Kernels of Coix lachrymal-jobi L. Cultivars - Guan-rong Li; Bao-hong Cao; Wei Liu; Rui-hua Ren; Jie Feng; Da-jin Lv (Current Microbiology, 2020)

Serotonin-induced miR-221/222 contribute to the activation of hepatic stellate cells - Yi Xiang; Yu-Shui Ma; Ji-Bin Liu; Zhi-Jun Wu; Xiao-Ping Wang; Li-Ping Liu; Gao-Ren Wang; Da Fu; Wei Shi (Biologia, 2020)

Sideswiping Tropical Cyclones and Their Associated Precipitation over China - Tian Feng; Fumin Ren; Da-Lin Zhang; Guoping Li; Wenyu Qiu; Hui Yang (Advances in Atmospheric Sciences, 2020)

Correction to: NaCl-induced stress: physiological responses of six halophyte species in in vitro and in vivo culture - Yuping Xiong; Hanzhi Liang; Haifeng Yan; Beiyi Guo; Meiyun Niu; Shuangyan Chen; Shuguang Jian; Hai Ren; Xinhua Zhang; Yuan Li; Songjun Zeng; Kunlin Wu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

NaCl-induced stress: physiological responses of six halophyte species in in vitro and in vivo culture - Yuping Xiong; Hanzhi Liang; Haifeng Yan; Beiyi Guo; Meiyun Niu; Shuangyan Chen; Shuguang Jian; Hai Ren; Xinhua Zhang; Yuan Li; Songjun Zeng; Kunlin Wu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Permo–Triassic granitoids of the Xing’an–Mongolia segment of the Central Asian Orogenic Belt, Northeast China: age, composition, and tectonic implications - Qiu-Ming Pei; Shou-Ting Zhang; Ken-ichiro Hayashi; Hua-Wen Cao; Dong Li; Li Tang; Xin-Kai Hu; Hao-Xing Li; Da-Ren Fang (International Geology Review, 2018)

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)

Enhancing the effectiveness of flood road gauges with color coding - Fang Jing; Li-Zhuang Yang; Ya-Li Peng; Ying Wang; Xiaochu Zhang; Da-Ren Zhang (Natural Hazards, 2017)

Anti-hepatocarcinoma activity of TT-1, an analog of melittin, combined with interferon-α via promoting the interaction of NKG2D and MICA - Lan-lan Wan; Da-qi Zhang; Jin-nan Zhang; Li-qun Ren (Journal of Zhejiang University-SCIENCE B, 2017)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

Bioavailability of sedimentary phosphorus under repeated sediment resuspension with the addition of algae - Wu Xiao-Fei; Li Da-Peng; Wang Ming; Wang Ren (Environmental Science and Pollution Research, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Management of differentiated thyroid carcinoma with bone metastasis: a case report and review of the Chinese literature - Wei-dong Zhang; Da-ren Liu; Cheng-cheng Feng; Chuan-biao Zhou; Chen-ni Zhan; Ri-sheng Que; Li Chen (Journal of Zhejiang University-SCIENCE B, 2014)

HER-2 overexpression and survival in colorectal cancer: a meta-analysis - Chao Li; Da-ren Liu; Long-yun Ye; Ling-na Huang; Sanjay Jaiswal; Xiao-wen Li; Hou-hong Wang; Li Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Systematic review of laparoscopy-assisted versus open gastrectomy for advanced gastric cancer - Long-yun Ye; Da-ren Liu; Chao Li; Xiao-wen Li; Ling-na Huang; Sheng Ye; Yi-xiong Zheng; Li Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

Molecular characterization and expression analysis of GlHMGS, a gene encoding hydroxymethylglutaryl-CoA synthase from Ganoderma lucidum (Ling-zhi) in ganoderic acid biosynthesis pathway - Ang Ren; Xiang Ouyang; Liang Shi; Ai-Liang Jiang; Da-Shuai Mu; Meng-Jiao Li; Qin Han; Ming-Wen Zhao (World Journal of Microbiology and Biotechnology, 2013)

Saline conducted electric coagulation (SCEC): original experience in experimental hepatectomy - Guo-ping Ding; Li-ping Cao; Da-ren Liu; Ri-sheng Que (Journal of Zhejiang University-SCIENCE B, 2012)

Effects of average velocity on the growth and surface topography of biofilms attached to the reclaimed wastewater drip irrigation system laterals - Gui Bing Li; Yun Kai Li; Ting Wu Xu; Yao Ze Liu; Hai Jin; Pei Ling Yang; Da Zhuang Yan; Shu Mei Ren; Zhi Fang Tian (Irrigation Science, 2012)

Surface topographic characteristics of suspended particulates in reclaimed wastewater and effects on clogging in labyrinth drip irrigation emitters - Yun Kai Li; Yao Ze Liu; Gui Bing Li; Ting Wu Xu; Hai Sheng Liu; Shu Mei Ren; Da Zhuang Yan; Pei Ling Yang (Irrigation Science, 2012)

pp5644 Interacts with phosphatidylinositol-4-phosphate adaptor protein-1 associated protein-1 - Xiao-Xia Ye; Hong Lu; Yao Yu; Ning Ding; Nai-Ling Zhang; Ke-Ke Huo; Da-Fang Wan; Yu-Yang Li; Jian-Ren Gu (Molecular and Cellular Biochemistry, 2005)